Analisis Kesiapan Berwirausaha Mahasiswa Kewirausahaan: Studi Kualitatif pada Konteks Pendidikan Tinggi - Mu'tamim, Nurul; Sari, Sefni Novita (Universitas Hamzanwadi, 2025)
This study is motivated by the gap between formal entrepreneurship education and the actual readiness of students to become entrepreneurs. The aim of this study is to explore the entrepreneurial readiness of 2024 entrepreneurship students at Universitas PGRI Sumatera Barat. A descriptive qualitative approach was used, with purposive sampling for participant selection. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using interactive analysis techniques. The results reveal that student readiness is shaped through complex interactions between internal motivation, self-efficacy, campus and family support, and project-based learning experiences. However, challenges such as fear of failure and lack of practical experience remain key obstacles. This study highlights the need for contextual, practical, and socially integrated entrepreneurship education. The implication is the importance of strengthening the curriculum and campus entrepreneurial ecosystem to produce graduates who are genuinely prepared to compete in the business world.